Tokenism Perception Scale: Validity and Reliability Study - Ozdemir, Tuncay Yavuz; Gurbuz, Oguz; Dogan, Abdulvahap (Ozgen Korkmaz, 2025)
Tokenism can be defined as the activity of opening the way for numerical minority individuals to become visible, in order to demonstrate the existence of a perception of diversity and inclusion in organizations and to help that organization appear tolerant or inclusive. The concept of tokenism; previously, emerged only from the disadvantages of being a woman, but with ongoing research, it has been determined that many different variables cause this perception within the organization. In this research, it was aimed to develop a valid and reliable measurement tool that can determine the level of teachers' perception of tokenism. In this research, an exploratory sequential design was used, combining both qualitative and quantitative research designs. The study group of the research consists of 304 teachers working in Malatya during the Exploratory Factor Analysis (EFA) phase and 306 teachers working in Elazig province during the Confirmatory Factor Analysis (CFA) phase. While creating the item pool, a literature review was conducted and the scale items were created based on this literature. These items were submitted to expert opinion to ensure content validity. As a result of EFA conducted to determine construct validity, a 3-factor structure consisting of 14 items was obtained. This structure was tested in a different sample group. As a result of CFA, it was determined that the fit values were at an acceptable level. In light of these data, it has been determined that the Tokenism Perception Scale is a valid and reliable measurement tool. © 2025, Ozgen Korkmaz. All rights reserved.
Keywords: reliability; scale development; tokenism; tokenism perception scale; validity